1983
DOI: 10.1002/art.1780260407
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of serum antibodies to the keratin layer of rat esophagus in patients with rheumatoid arthritis

Abstract: Serum antibodies reactive with the keratin layer of rat esophagus (AKA) were found in 46 of 80 (57.5%) rheumatoid arthritis (RA) patients. In contrast, A M were present in only 7 of 82 (9.5%) patients with other types of rheumatic disorders and in 2 of 47 (4.2%) healthy subjects. AKA were not specific for RA, however, because in the former group, A M were present in 4 of 20 (20%) systemic sclerosis patients and in 3 of 12 (25%) ankylosing spondylitis patients. AKA belong predominantly to the IgG class and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 17 publications
1
22
0
1
Order By: Relevance
“…Using indirect immunofluorescence, antibodies of the IgG class directed against components of rat esophagus and human skin have been described as highly specific for RA (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Until now, the presence of these autoantibodies, the so-called "antikeratin antibodies," in the serum of patients is the most specific serological criterion for the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using indirect immunofluorescence, antibodies of the IgG class directed against components of rat esophagus and human skin have been described as highly specific for RA (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Until now, the presence of these autoantibodies, the so-called "antikeratin antibodies," in the serum of patients is the most specific serological criterion for the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In 1979, Young et al (6) showed, using indirect immunofluorescence, the presence, in rheumatoid sera, of IgG antibodies labeling the stratum corneum of rat esophagus epithelium. These antibodies are clearly autoantibodies since they also react with the stratum corneum of human epidermis (6)(7)(8)(9). They have been found to be highly specific for the disease (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and their detection is now widely used as a diagnostic test for RA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These antibodies were therefore catted antikeratin antibodies (AKA), in the absence of any biochemical characterization of the antigen they recognized. However, this labelting was found to be unmodified either by pretreatment of rat oesophagus cryosections with a rabbit anti-serum to human cytokeratins, or by preabsorption ofthe RA sera with human cytokeratins [5]. In a recent work.…”
Section: Introdlctionmentioning
confidence: 98%
“…IgG antibodies to the cornified epithelium of rat oesophagus have been largely demonstrated to occur specifically in rheumatoid arthritis (RA) sera ( [2][3][4][5][6][7][8][9][10][11][12][13], reviewed in [14]). The RA-specific antibodies show a typical indirect immunofluorescence (T!F) labetling pattern restricted to the upper epithetiat tayer, the stratum corneum.…”
Section: Introdlctionmentioning
confidence: 99%